Analytical and Empirical Foundations for a Debate upon the VAT Reform in Colombia (Papeles, 2021)
Colombia has a structural deficit. It requires a deep tributary reform, which is ignored by the government, since it must check the fiscal covenant with companies, with the richest one percent and one per thousand people of the country. For the national government, it is easier to charge all the food basket in the general fee of 19%. The valued added tax, as well as the consumption one, are regressive taxes, since they are paid by the final consumers, regardless of their level of income. For that reason, the detailing results of income concentration in Colombia and the increase of poverty are presented here. Such results were produced by a simulation exercise with the microdata of the last National Household Survey.
Keywords: Tributary Reform; Valued Added Tax; NHS; Income; VAT